2001
DOI: 10.1034/j.1600-0501.2001.012001019.x
|View full text |Cite
|
Sign up to set email alerts
|

Implant‐supported overdentures, a prevention of bone loss in edentulous mandibles?

Abstract: 1) the increased function after this treatment seems to cause a load-related bone formation which minimizes the physiologic age-related mandibular BMC loss, 2) this effect seems to be independent of attachment system and 3) mandibular osteoporosis prior to implant treatment may be a risk factor for bone loss around implants. However, this treatment can be recommended also in osteoporotic persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 32 publications
2
86
0
5
Order By: Relevance
“…Although many authors have suggested that immediate implant placement in fresh extraction sockets can prevent physiological bone resorption following the extraction of a dental element, more recent studies have questioned this possibility [13][14][15][16][17][18].…”
mentioning
confidence: 99%
“…Although many authors have suggested that immediate implant placement in fresh extraction sockets can prevent physiological bone resorption following the extraction of a dental element, more recent studies have questioned this possibility [13][14][15][16][17][18].…”
mentioning
confidence: 99%
“…No, nepravodobnom dijagnozom resorpcije grebeni se mogu resorbirati do tih razmjera da postaju nepovoljni ~ak i za ugradnju implantata kojima bi se osigurala dovoljna retencija i stabilizacija protetskih nadomjestaka, odnosno njihova adekvatna funkcija (16,17).…”
Section: Imbenici Koji Utje^u Na Gubitak Ko[tane Mase ^Eljustiunclassified
“…And that it can slow down atrophy of the alveolar bone in comparison with conventional treatment [20][21][22].…”
Section: Problemmentioning
confidence: 99%